Development of Monopoly Game Media in Visual Based Arabic Language Learning to Improve Vocabulary Mastery - Zakiah Nur Harahap; Rahmaini Rahmaini (Universitas Muhammadiyah Enrekang, 2023)
This research is aimed at developing a game-based learning media, one of which is the monopoly game. This product is modified from the original game into an educational game that is used as a learning medium to help increase interest in learning to memorize Arabic vocabulary, especially MTs. Researchers use the ADDIE development model which has five stages, namely analysis, planning, design, implementation and evaluation. Analysis data was obtained through in-depth interviews and observations and obtained using descriptive quantitative methods to obtain valid results for the product. The results of the research show that the Monopoly game media can make it easier for students to memorize Arabic vocabulary, increase their interest in learning and make the class atmosphere more enjoyable.